Phase equilibria and thermodynamic description of solid dispersions of 8-hydroxyquinoline – 4-chlorobenzoic acid drug system - Salim, S.S.; Shekhar, H. (Journal of Drug Delivery and Therapeutics, 2019)
In present article 8-hydroxyquinoline (HQ)-4-chlorobenzoic acid (CBA) binary drug system has been undertaken to study phase diagram and thermodynamic contribution in the system in terms of partial and integral mixing and excess functions. The phase equilibria of the system undertaken shows the formation of 1:1 addition compound C and its eutectic E at 214º and199º c respectively. The negative value of molar free energy of mixing (∆GM) of solid dispersion at 0.810 and 0.895 mole fraction of CBA suggests that the mixing in these cases is spontaneous. The integral molar enthalpy of mixing value corresponds to the value of excess integral molar free energy of the system favors the regularity in the binary solutions. The positive value of excess free energy (gE) for all the eutectic and noneutectic solid dispersion suggests an association of weaker nature between unlike molecules and of stronger nature between like molecules. Gibbs-Duhem equation gives the graphical solution of partial molar heat of mixing (Hi-M), activity and activity coefficient of a particular constituent in the binary mix. Interfacial roughness of the binary solid dispersion has also been explained.Keywords: Binary drug dispersion, phase diagram, activity, activity coefficient, mixing and excess function.